Analysis of Customer Satisfaction Levels Towards the Parking System at Ittelkom Surabaya using Servqual Methods - Cahyani, Nabilla Adinna; Zunaidi, Rizqa Amelia; Muttaqin, Benazir Imam Arif (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
ITTelkom Surabaya is a campus that was established in 2018. The increasing number of students can affect the quality of parking lots that can be accommodated. Based on data on parking attendants' quality and service satisfaction, students feel dissatisfied due to the many shortcomings in the facilities and quality of service in parking at ITTelkom Surabaya. This study aims to measure service quality and analyze which factors affect customer satisfaction with the parking system at ITTelkom Surabaya. This research is conducted using quantitative analysis with the Servqual method. Questionnaire forms were distributed to parking lot users in data collection, and the data were collected from students. The existence of this research can be used as an evaluation material to develop the satisfaction of the parking system as measured. The results showed that measuring the service quality of the vehicle parking system at ITTelkom Surabaya still needs improvement. The gap value in some statement attributes shows that the parking system's customer service quality still needs to meet expectations. Then, the factors that impact customer satisfaction with the parking system at ITTelkom Surabaya are the variables X1 (Tangible) and X3 (Responsiveness). Both variables have a low significance T-test value, so there needs attention to improving and evaluating the parking system at ITTelkom Surabaya to fulfill customer wants and needs.